Imbalance of Interests Between Grain Producing and Consuming Regions and the New Mission of Urban Agriculture: A Perspective From Marxist Ground Rent Theory - Bohan Wang (Journal of Frontier in Economic and Management Research, 2025)
Food security serves as a critical pillar of national security.In China’s food supply sector,phenomena such as “major grain producers but minor industrial players and fiscally constrained entities,”“economic disincentives for grain cultivation,”and “increased production not necessarily translating into higher income”reflect a fundamental imbalance in benefit distribution between production and consumption regions.This imbalance essentially stems from the contradiction between “value generated from land” and “equitable value distribution.”Using the Marxist theory of land rent as an analytical framework, this study analyzes the systematic rent drain from producing regions through a three-dimensional lens comprising absolute rent, differential rent (I & II), and monopoly rent. Guided by this perspective, and introducing the role of urban agriculture as a strategic vehicle for rebalancing, we propose an institutionalized compensation mechanism centered on urban agriculture and supported primarily by horizontal fiscal transfer payments.This approach aims to enhance new quality agricultural productivity,address the challenge of “economic disincentives for grain cultivation”,and ensure that major grain-producing regions receive fair economic returns based on land ownership and ecological contributions.By rebalancing interests between production and consumption areas,the mechanism seeks to safeguard national food security and promote urban-rural integration.It should be noted, however,that while an urban agriculture model grounded in land rent theory offers a viable pathway for mitigating regional benefit imbalances and boosting advanced agricultural productivity,it is not the sole determinant.